POETIC AND LOGIC INTUITIONS OF “THE RIGVEDA” - Пилип’юк, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article describes the poetic and logic features of "Rigveda", communicative and cognitive approaches to the study of the ancient Indian religious monument.